2014
DOI: 10.1007/s11207-014-0519-5
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Differences in Absolute Irradiance Measurements Between the SOHO/CELIAS/SEM and the SDO/EVE

Abstract: The Solar EUV Monitor (SEM) onboard SOHO has measured absolute extreme ultraviolet (EUV) and soft X-ray solar irradiance nearly continuously since January 1996. The EUV Variability Experiment (EVE) on SDO, in operation since April of 2010, measures solar irradiance in a wide spectral range that encompasses the band passes (26 – 34 nm and 0.1 – 50 nm) measured by SOHO/SEM. However, throughout the mission overlap, irradiance values from these two instruments have differed by more than the combined stated uncerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 38 publications
(56 reference statements)
0
19
0
Order By: Relevance
“…Recent studies (Snow et al 2014;Wieman et al 2014) showed that the rate of the dominant ionization process for helium, i.e., photoionization, may be biased by systematic instrumental effects. This topic is still a subject of research, but for now we cannot rule out that the ionization model we use is systematically biased upward or downward.…”
Section: Modification Of the Flux By The Collimatormentioning
confidence: 99%
“…Recent studies (Snow et al 2014;Wieman et al 2014) showed that the rate of the dominant ionization process for helium, i.e., photoionization, may be biased by systematic instrumental effects. This topic is still a subject of research, but for now we cannot rule out that the ionization model we use is systematically biased upward or downward.…”
Section: Modification Of the Flux By The Collimatormentioning
confidence: 99%
“…The SEM data processing algorithm for converting raw detector count rates to calibrated irradiance values is based on the NIST-measured channel spectral response functions, a time-and wavelength-dependent degradation model, and a solar reference spectrum that provides an appropriate spectral weighting of the response function and, in the case of the SEM 1 channels, a correction for sensitivity outside of the nominal 260-340 Å band pass. For further information on the SEM instrument, see references in Wieman et al (2014).…”
Section: The Semmentioning
confidence: 99%
“…In Wieman et al (2014) the aforementioned differences between SEM version 3.1 irradiance values and those from SDO EVE MEGS and EVE ESP were traced to inaccuracies in the SEM 1 instrument response function and in the solar reference spectrum used in data processing. Although the response function for the on-orbit SEM was measured prior to the launch of SOHO, a 2007 NIST calibration of the SEM sounding rocket clone instrument (which is nominally identical to the in-flight version) revealed that the SEM 1 sensitivity outside of its nominal 260-340 Å band pass is greater than what was measured pre-launch owing to the grazing incidence reflection off of a portion of the instrument housing that was left off for the original calibration.…”
Section: The Semmentioning
confidence: 99%
See 2 more Smart Citations